2017
DOI: 10.1016/j.electacta.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characteristics up to 4.8 V of layered LiNi1/3Co1/3Mn1/3O2 cathode materials for high voltage lithium-ion batteries

Abstract: Understanding the structure properties in deep delithiated states and electrochemical kinetics in the high potential window of LiNi1/3Co1/3Mn1/3O2 (NCM) cathode materials is essential to advance their performance in rechargeable lithiumion batteries for 5 V chemistry. Here we report a layered single-phase NCM showing great structural reversibility and without H3 phase formation when charged up to 4.8 V at least for 5 cycles. However, the poor cluster scale conductivity results in inactive material in thick ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
2
27
1
Order By: Relevance
“…Here the orthorhombic lattice is used to track the structural evolution. As shown by the blue dots labelled as Orth-1 phase in Figure 4a and 4b,u pt op attern #4 0, which corresponds to % 0.65 Li + extraction with very little oxygen oxidation, the reflections of Orth-1 phase shift only slightly,with the lattice changing slightly and smoothly,c orresponding to av ery flat charging plateau, typically associated with cationic redox, i.e., Co 2+/ Co 3+ .T he intensity is reduced significantly for the highindexed reflections such as 220 and 260, but the intensity reduction is small for the low-indexed reflections,c .f.F igure S10, suggesting ad isruption of structural details on the long-range correlation length even occurring at the early delithiation stage.T his behavior is different from the continuous solid-solution reaction in layered oxide Li(NiCoMn) 1/ 3 O 2 , [25] and the abrupt two-phase reaction in LiFePO 4 . [27] In the ensuing delithiation, as et of new reflections stem from another orthorhombic phase Orth-2, shown by the green dots in Figure 4a and b.…”
Section: Resultsmentioning
confidence: 83%
“…Here the orthorhombic lattice is used to track the structural evolution. As shown by the blue dots labelled as Orth-1 phase in Figure 4a and 4b,u pt op attern #4 0, which corresponds to % 0.65 Li + extraction with very little oxygen oxidation, the reflections of Orth-1 phase shift only slightly,with the lattice changing slightly and smoothly,c orresponding to av ery flat charging plateau, typically associated with cationic redox, i.e., Co 2+/ Co 3+ .T he intensity is reduced significantly for the highindexed reflections such as 220 and 260, but the intensity reduction is small for the low-indexed reflections,c .f.F igure S10, suggesting ad isruption of structural details on the long-range correlation length even occurring at the early delithiation stage.T his behavior is different from the continuous solid-solution reaction in layered oxide Li(NiCoMn) 1/ 3 O 2 , [25] and the abrupt two-phase reaction in LiFePO 4 . [27] In the ensuing delithiation, as et of new reflections stem from another orthorhombic phase Orth-2, shown by the green dots in Figure 4a and b.…”
Section: Resultsmentioning
confidence: 83%
“…Cation mixing shifts the hierarchical R-3m space group to the tightly packed spinel Fm-3m space group. This tight structure leads to shorter ion spacing and larger interactions, making Li + diffusion difficult (Zhang et al, 2017). Studies have suggested that structural changes occur on the surface of high nickel layered oxides Liu et al, 2020).…”
Section: Surface Structure and Evolution Of High-nickel Cathode Matermentioning
confidence: 99%
“…During charge, Li ions are constantly removed from the LiMO 2 structure, leading to the changes of lattice parameters. In general, the lattice parameter c expands first and then contracts, often to a value smaller than that of the pristine state at high voltage due to the nearly empty Li layer [159][160][161]; this may cause the structure collapse in c-axis direction leading to the irreversible damage of the structure and capacity fade. To solve this problem, studies were devoted to discover and design new materials aimed at reducing the c variation during cycling to achieve the high-capacity retention and long cycle life.…”
Section: Moomentioning
confidence: 99%